Ayurvedic Management of Switra (Vitiligo) - A Single case Study - Kumar, Anil; Chudasama, Hardik; Rai, Pankaj; Yadav, C R (International Research Journal of Ayurveda & Yoga, 2022)
Introduction -Vitiligo is the most widely known pigmentation disorder, and it is mentioned in Ayurveda as Shwitra for its characteristic appearance. It is caused by disturbance of all Tridosha along with Rakta, Mamsa, and Meda dhatu. Vitiligo, the most common de-pigmenting disorder, affects 0.5–1% of the worldwide population, causing disfigurement and serious disturbances in quality of life. It is harmless but a very serious cosmetic problem which affects the emotional, psychological, and social well-being of the affected person. Material and Method - A 32-year-old female diagnosed with Vitiligo (Shwitra), presented with complaints of increasing area and number of de pigmented patches of skin which was managed by following Ayurveda principles. A treatment protocol was designed based on the signs and symptoms observed in this patient. The protocol includes only Shamana treatment with a combination of powdered herbal drugs, viz., Bakuchi (Psoralea corylifolia), Manjistha (Rubia Cordifolia), Lodhra (Symplocos Racemosa) and Nagkesar (Pterocarpus marsupium) powder orally along with Arogyavardhini vati 500 mg twice in a day orally. For Local Application Bakuchi oil is administrated. Result and Discussion The treatment protocol was found to be effective in the reversal of de-pigmented patches to re-pigmentation, which may be adopted in future cases, using different combinations of drugs based upon the different Ayurvedic parameters to obtain even better results.